Thermopower Enhancement of Rutile-type SnO2 Nanocrystalline Using Facile Co-Precipitation Method - Nadya Larasati Kartika; Budi Adiperdana; Asep Ridwan Nugraha; Ardita Septiani; Dadang Mulyadi; Asep Rusmana; Pepen Sumpena; Dedi Dedi (Jurnal Elektronika dan Telekomunikasi, 2020)
Metal oxide semiconductor has attracted so much attention due to its high carrier mobility. Herein, thermoelectric study of nanocrystalline SnO2 through a simple co-precipitation method is conducted to enhance the Seebeck coefficient (S). X-ray diffraction, thermogravimetric analysis (TGA), resistivity (r), Seebeck coefficient (S), and power factor (PF) measurements are conducted to analyze the thermoelectric properties of the material. The measurements show that there are two interesting results, which are the unusual resistivity behavior and the high value of the S. Resistivity behavior shows a non-reflective intermediate semiconductor-metals behavior where the turning point occurs at 250 o C. This behavior is strongly correlated to the surface oxide reaction due to annealing temperature. The maximum S likely occurs at 250 ºC, since the curve shows a slight thermopower peak at 250 ºC. The value of the S is quite high with around twenty times higher than other publications about SnO2 thermoelectric material, this happens due to the bandgap broadening. The energy gap of SnO2 calculated using density functional theory (DFT), which was performed by Quantum Espresso 6.6. The result shows that there is a broadening energy gap at different momentum or wave factor. Nanocrystalline semiconductors material is giving an impact to increase the width of bandgap due to quantum confinement and could enhance the thermopower especially in SnO2 nanocrystalline